Constructive Side-Channel Analysis and Secure Design 6th International Workshop, COSADE 2015, Berlin, Germany, April 13-14, 2015. Revised Selected Papers - Mangard, Stefan; Poschmann, Axel Y.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2015)
This book constitutes the thoroughly refereed post-conference proceedings of the 6th International Workshop, COSADE 2015, held in Berlin, Germany, in April 2015. The 17 revised full papers presented were carefully selected from 48 submissions. the focus of this workshop was on following topics: side-channel attacks, FPGA countermeasures, timing attacks and countermeasures, fault attacks, countermeasures, and Hands-on Side-channel analysis.
Side-Channel Attacks -- Improving Non-Profiled Attacks on Exponentiations Based on Clustering and Extracting Leakage from Multi-Channel High-Resolution EM Measurements -- Template Attacks vs. Machine Learning Revisited (and the Curse of Dimensionality in Side-Channel Analysis) -- Efficient Selection of Time Samples for Higher-Order DPA with Projection Pursuits -- Exploring the Resilience of Some Lightweight Ciphers Against Profiled Single Trace Attacks -- Two Operands of Multipliers in Side-Channel Attack -- FPGA Countermeasures -- Evaluating the Duplication of Dual-Rail Precharge Logics on FPGAs -- Side-Channel Protection by Randomizing Look-Up Tables on Reconfigurable Hardware -- Timing Attacks and Countermeasures -- A Faster and More Realistic Flush+Reload Attack on AES -- Faster software for fast endomorphisms -- Toward Secure Implementation of McEliece Decryption -- Fault Attacks -- Fault Injection with a new favor: Memetic Algorithms make a difference -- Differential Fault Intensity Analysis on PRESENT and LED Block Ciphers -- A Biased Fault Attack on the Time Redundancy Countermeasure for AES -- Countermeasures -- Faster Mask Conversion with Lookup Tables -- Towards Evaluating DPA Countermeasures for Keccak on a Real ASIC -- Hands-on Side-Channel Analysis Side-Channel Security Analysis of Ultra-Low-Power FRAM-based MCUs -- Side Channel Attacks on Smartphones and Embedded Devices using Standard Radio Equipment.
Keywords: Computer science; Computer communication systems; Computer security; Data encryption (Computer science).; Algorithms; Computer science -- Mathematics; Management information systems; Computer Science; Data Encryption; Computer Communication Networks; Systems and Data Security; Management of Computing and Information Systems; Algorithm Analysis and Problem Complexity; Discrete Mathematics in Computer Science; Electronic books